Risk factors for the delayed onset of neuropsychologic sequelae following carbon monoxide poisoning. Issue 4 (26th April 2016) - Kitamoto, Takeshi; Tsuda, Masanobu; Kato, Masaki; Saito, Fukuki; Kamijo, Yoshito; Kinoshita, Toshihiko
Abstract : Aim: Carbon monoxide (CO) poisoning often manifests delayed neuropsychological sequelae. The risks and preventive factors for the development of delayed neuropsychological sequelae are controversial at present. The purpose of this retrospective study was to assess the risk factors for this condition. Method: We studied 81 patients with CO poisoning admitted to the Critical Care and Emergency Medicine Center at the Kansai Medical University from 2006 to 2012. All patients (64 males and 17 females; average age, 45.9 years) were divided into non‐ delayed neuropsychological sequelae and delayed neuropsychological sequelae groups and retrospectively studied. Patient data were analyzed by univariate and multivariate analyses. Results: The results of our study indicated that prolonged CO exposure, elevated serum creatinine phosphokinase levels, head image abnormality in the basal ganglion or white matter region, low Glasgow Coma Scale score, bedsore occurrence, and CO poisoning attributable to burning charcoal were each predictive risk factors for the development of delayed neuropsychological sequelae. Bedsore occurrence and serum creatinine phosphokinase elevation were significant risk factors by multivariate analysis, whereas no significant differences were found for age, gender, mean blood pressure, heart rate, arterial carboxyhemoglobin and lactate concentrations, or base excess. Conclusion: We identified several predictive risk factors of delayed neuropsychological sequelae. We believe that these factors will contribute to identifying optimum therapeutic methods and follow‐up terms for patients with acute CO poisoning at risk of developing delayed neuropsychological sequelae.